2000
DOI: 10.1093/toxsci/55.2.320
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Benzo[a]pyrene and Its Hydroxylated Metabolites in an Estrogen Receptor-alpha Reporter Gene Assay

Abstract: A human breast cancer cell line, MCF-7, transiently transfected with a chimeric estrogen receptor (Gal4-HEG0) and a luciferase reporter plasmid (17m5-G-Luc), was used to investigate the estrogenic activity of benzo[a]pyrene (B[a]P), a prototypical polyaromatic hydrocarbon (PAH). B[a]P at concentrations > or = 1 microM produced responses comparable to that of 0.1 nM 17beta-estradiol (E2). The ER antagonist ICI 182,780 (ICI) completely inhibited the response to both E2 and B[a]P, indicating that the responses we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
93
2
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(110 citation statements)
references
References 35 publications
5
93
2
6
Order By: Relevance
“…Polychlorinated biphenyls are converted to hydroxylated metabolites in animals, and some hydroxylated polychlorinated biphenyls show estrogenic and/or antithyroid hormonal activity (Connor et al 1997;Garner et al 1999;Korach et al 1988). Further, methoxychlor, trans-stilbene, benzophenone, and benzo [a]pyrene are proestrogens that require metabolic activation by liver microsomal mixed-function oxidase in animals (Charles et al 2000;Fertuck et al 2001;Gaido et al 1999;Nakagawa and Suzuki 2002;Sugihara et al 2000). In contrast, the estrogen screening Weights of the reproductive organs of rats were expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Polychlorinated biphenyls are converted to hydroxylated metabolites in animals, and some hydroxylated polychlorinated biphenyls show estrogenic and/or antithyroid hormonal activity (Connor et al 1997;Garner et al 1999;Korach et al 1988). Further, methoxychlor, trans-stilbene, benzophenone, and benzo [a]pyrene are proestrogens that require metabolic activation by liver microsomal mixed-function oxidase in animals (Charles et al 2000;Fertuck et al 2001;Gaido et al 1999;Nakagawa and Suzuki 2002;Sugihara et al 2000). In contrast, the estrogen screening Weights of the reproductive organs of rats were expressed.…”
Section: Discussionmentioning
confidence: 99%
“…PAHs were the major chemical group found in this fraction (Wang et al, 2003). Several PAHs, including benzo[α]pyrene (BaP) and benz [α]anthracene (BaA), or their oxygenated derivatives, have been shown to act as estrogenic compounds in ER-regulated receptor gene assays (Chaeles et al, 2000). Recently, several other PAHs, including fluorine, fluoranthene, pyrene, chrysene, phenanthrene and anthracene, were found to act as very weak inducers of ER-mediated activity in MCF-7 cells (Vondráček et al, 2002).…”
Section: Estrogenic Activity Of Sediment Samplesmentioning
confidence: 99%
“…The Th2 shift in the group with the highest dose of B[a]P through the estrogenic activity of this PAH was also possible as estrogen alone may have this effect (Huber et al, 1999;Salem, 2004). Several recent studies have reported that some PAHs, including B[a]P can activate estrogen receptors, either directly or indirectly by producing estrogenic metabolites (Charles et al, 2000;Fertuck et al, 2001;Pliskova et al, 2005).…”
Section: Discussionmentioning
confidence: 96%